Bioprospection of Diospyros discolor Willd. fruit for the biosynthesis of silver nanoparticles. Issue 1 (March 2020) - Nolia, I; Handayani, W; Secario, K; Djuhana, D; Imawan, C
Abstract: Leaves from Diospyros discolor Willd. plants can act as a reducing agent in the biosynthesis of silver nanoparticles. This raises the question of whether other parts of the plant can also be used for this purpose. The present study aimed to explore the prospect of D. discolor fruit for the synthesis of silver nanoparticles. The fruit and seeds of the plant were extracted and used for the biosynthesis process, and the resulting silver nanoparticles were characterized using UV–visible light spectrophotometry, Transmission electron microscopy (TEM), and particle size analysis (PSA). During biosynthesis, aqueous extracts from the fruit flesh or seeds were reacted with 1 mM silver nitrate at various ratios. A ratio of 1:2 (v/v) resulted in the highest absorbance values (indicating the greatest production of nanoparticles), and the absorbance at all ratios increased with time. The results were similar for the fruit flesh and seed extracts, with absorbance values observed in the same peak areas for each treatment. However, the use of D. discolor fruit flesh resulted in faster reactions during the initial 24 h.